Melitta Weiss Adamson, ed.: Regional Cuisines of Medieval Europe - Davidson, Alan (Petits Propos Culinaires, 2024)
Melitta Weiss Adamson, ed.: Regional Cuisines of Medieval Europe: Routledge, 2002: ISBN 0-415-92994-6: 254 pp., h/b, $85.